The Character, Organization Change and Information System - Santo Fernandi Wijaya (ComTech: Computer, Mathematics and Engineering Applications, 2011)
The success of building an integrated information system is an expectation of every company management to achieve effective and efficient working system. However, in the real business practices, not a few companies failed in building an integrated information system caused by the absence of several factors: strong commitment, hard work and smart effort conducted by a team. The team determines the success level in building an integrated information system. A factor of intelligence and mental maturity of users in running a new information system that has not been known is also another key to success. Therefore, it takes a good user’s character supported by a management decision to make management changes to achieve the building success level. This study aims to address the role of character and organization changes in achieving a success building an integrated information system.